Prevalence of obesity and overweight among type 2 diabetic patients in Bisha, Saudi Arabia - AlShahrani, Mohammad S. (J Family Med Prim Care, 2021)
CONTEXT: Obesity is a significant worldwide public health issue and one of the significant risk factors for type 2 diabetes and cardiovascular diseases. AIMS: This study aims to determine the prevalence of obesity and overweight among type 2 diabetic patients, and explore the association between Body Mass Index (BMI), social demographics and time since diagnosis. SETTINGS AND DESIGN: This study followed a cross-sectional study design in Bisha, Saudi Arabia. METHODS AND MATERIAL: Participants were identified by convenience sampling from 6 Primary Health Care Centers (PHCC) over a period of two weeks from March 16 to March 28, 2020. STATISTICAL ANALYSIS USED: Frequency and percentage were used to report the obesity prevalence. Chi-Square test was used to test the association between social demographics and time since diagnosis with BMI. RESULTS: Obesity and overweight prevalence was 85.8% (n = 525), among which 27.9% (n = 171) were overweight, 57.8% were obese (n = 354), and only 13.2% (n = 81) had normal weight. A statistically significant difference between BMI and age was observed (P = 0.01). Differences between BMI and time since obesity diagnosis were statistically significant (P < 0.0001). Differences between BMI and time since type 2 diabetes diagnosis were not found to be statistically significant. CONCLUSION: There is a high prevalence of obesity and overweight among type 2 diabetic patients in Bisha. Differences in BMI were found to be statistically significant according to age, gender, education level and time since obesity diagnosis. Patient education programs and public health awareness about diabetes and obesity are highly recommended.